PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM MENUMBUHKEMBANGKAN SIKAP TAWAZUN DI SMP AL-KAUTSAR BANYUWANGI - Lukman Hakim; Maskuri Maskuri; Yorita Febry Lismanda (VICRATINA, 2019)
Education essentially takes place in a process. The process consists of transforming the values of technological knowledge and skills. The acceptance process is students who are growing and developing towards the direction of personality maturity and mastery of knowledge. This thesis discusses the role of Islamic religious education teachers in developing tawazun attitudes at Al-Kautsar Banyuwangi  junior School. the role of Islamic religious education teachers in developing tawazun attitudes at Al-Kautsar Banyuwangi junior School. The research objectives are 1) To find out how the teaching plans of Islamic religious education teachers in developing tawazun attitudes at Al-Kautsar Banyuwangi Junior School, 2) To find out how the implementation of Islamic education in developing tawazun attitudes in Al-Kautsar Banyuwangi Junior School, 3) To know Islamic religious education evaluation system in developing tawazun attitudes in Al-Kautsar Banyuwangi Junior School, 4) To find out how the results of Islamic religious education in developing tawazun attitudes at Al-Kautsar Junior School in Banyuwangi. This research is a qualitative descriptive study. The subject of this research was a teacher of Islamic religious education. Data collection methods used in the study were observation, interviews, and documentation. The results showed that the role of Islamic religious education teachers in developing tawazun attitudes at Al-Kautsar Banyuwangi junior School was: teachers as instructor planners, educators, role models, learning resources, motivators, facilitators, evaluators. Keywords: islamic education, teachers, tawazun